Photodynamic Therapy in the Treatment of Cancer-The Selection of Synthetic Photosensitizers - David Aebisher; Iga Serafin; Katarzyna Batóg-Szczęch; Klaudia Dynarowicz; Ewa Chodurek; Aleksandra Kawczyk-Krupka; Dorota Bartusik-Aebisher (MDPI AG, 2024)
Photodynamic therapy (PDT) is a promising cancer treatment method that uses photosensitizing (PS) compounds to selectively destroy tumor cells using laser light. This review discusses the main advantages of PDT, such as its low invasiveness, minimal systemic toxicity and low risk of complications. Special attention is paid to photosensitizers obtained by chemical synthesis. Three generations of photosensitizers are presented, starting with the first, based on porphyrins, through the second generation, including modified porphyrins, chlorins, 5-aminolevulinic acid (ALA) and its derivative hexyl aminolevulinate (HAL), to the third generation, which is based on the use of nanotechnology to increase the selectivity of therapy. In addition, current research trends are highlighted, including the search for new photosensitizers that can overcome the limitations of existing therapies, such as heavy-atom-free nonporphyrinoid photosensitizers, antibody-drug conjugates (ADCs) or photosensitizers with a near-infrared (NIR) absorption peak. Finally, the prospects for the development of PDTs are presented, taking into account advances in nanotechnology and biomedical engineering. The references include both older and newer works. In many cases, when writing about a given group of first- or second-generation photosensitizers, older publications are used because the properties of the compounds described therein have not changed over the years. Moreover, older articles provide information that serves as an introduction to a given group of drugs.